Life Insurance, Precautionary Saving and Contingent Bequest - Fwu-Ranq Chang (Center for Economic Studies and ifo Institute (CESifo), 2001)
Purchasing life insurance is for the welfare of young children, par-ticularly preteens, who are liquidity constrained. In this paper, we present a life cycle model of life insurance that takes into account the ages of these young beneciaries. We show that, as the child ages, the need for protection is reduced and, consequently, the size of contingent bequest may shrink. The demand for life insurance is positively related to the number, age differentials, living standards, and the time needed to reach adulthood. Also, the breadwinner's life-time uncertainty and the unfairness of the insurance market encourage precautionary saving.
Keywords: 330; Loading factor; birth order; actuarial rate of interest; and the age of independence